2017
DOI: 10.1007/s41742-017-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–Temporal Distribution of Polycyclic Aromatic Hydrocarbons in Urban Soils in Cape Town, South Africa

Abstract: The spatial and seasonal distribution of eight US Environmental Protection Agency priority poly aromatic hydrocarbons (PAHs); namely benzo(b)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, benzo(k)fluoranthene, chrysene, benzo(a)anthracene, dibenz(a,h)anthracene and fluoranthene were investigated in 35 soil samples. Gas chromatography with flame ionization detection was used for the quantification of the PAHs in the residential, roadside and industrial soil samples collected in proximity to an industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The BaA in the environment has been attributed to human use of fossil fuel and derived products, along with industrial processes including petroleum cracking (Verbruggen and Van Herwijnen 2012). This was similar to the findings of Omores et al (2017), who reported BaA as the dominant PAH congener in urban soils from Cape Town, South Africa. Our results also showed that the total concentration of noncarcinogenic PAHs (naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, and pyrene) was 277.75 µg/kg, and concentrations of weakly carcinogenic (chrysene), carcinogenic (BaA, BbF, BkF, IP, and DahA), and strongly carcinogenic (BaP) PAHs were 85.93, 357.35, and 2.4 µg/kg, respectively (Means 1989).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The BaA in the environment has been attributed to human use of fossil fuel and derived products, along with industrial processes including petroleum cracking (Verbruggen and Van Herwijnen 2012). This was similar to the findings of Omores et al (2017), who reported BaA as the dominant PAH congener in urban soils from Cape Town, South Africa. Our results also showed that the total concentration of noncarcinogenic PAHs (naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, and pyrene) was 277.75 µg/kg, and concentrations of weakly carcinogenic (chrysene), carcinogenic (BaA, BbF, BkF, IP, and DahA), and strongly carcinogenic (BaP) PAHs were 85.93, 357.35, and 2.4 µg/kg, respectively (Means 1989).…”
Section: Resultssupporting
confidence: 92%
“…Several concentrations of PAH have been reported in topsoil and various environmental compartments from a number of cities around the world, underscoring the fact that PAH pollution is a major environmental concern especially in urban areas and cities with high levels of anthropogenic activities (Alegbeleye et al 2017). Some of these regions include China (Tang et al 2005;Zheng et al 2014;Wang et al 2015Wang et al , 2017, South Korea (Nam et al 2003), India (Gune et al 2019;Tarafdar and Sinha 2019), Portugal (Cachada et al 2012), Germany (Martens et al 1997), United Kingdom (Lorenzi et al 2010), Ghana (Bortey-Sam et al 2014;Bandowe and Nkansah 2016), South Africa (Nieuwoudt et al 2011;Okedeyi et al 2013;Munyengabe et al 2017;Omores 2017), and Kenya (Mungai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The PAHs levels in the concentrated extracts were determined using Agilent 7820A gas chromatograph (GC) coupled with flame ionization detector (Olatunji et al 2014; Coelho et al 2008; Essumang 2010; Nekhavhambe et al 2014; Omores et al 2017). A HP-5 fused silica capillary column (30 m × 0.320 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…The high road density in cities is associated with soil contamination, with various transport-related substances, such as heavy metals and polycyclic aromatic hydrocarbons (PAHs), among others [64,65]. Recently, traffic-related pollution has been linked not only with fuel combustion, but also with tire and road wear particles (TRWP) [66].…”
Section: Contamination Ph Changes Nutrient Deficiencymentioning
confidence: 99%